Modification of Activated Carbon for the Adsorption of Humic Acid - H.M.B. Eustáquio; Christian W. Lopes; Rafael S. da Rocha; Brena D. Cardoso; Sibele B.C. Pergher (Adsorption Science & Technology)
Commercial activated carbon treated with sulphuric and phosphoric acids was used to remove humic acids (HAs) from water. To achieve this goal, the iodine indices of treated and untreated materials were characterized by X-ray diffraction and nitrogen physisorption. Adsorption assays for HAs evaluated the quantities adsorbed after a fixed time. Temporal evolution of HA adsorption was determined from the adsorption kinetics. Experimental results indicated that the sulphuric acid treatment was more efficient and had a higher HA adsorption at each time point evaluated. Evaluating the specific area helped to verify this fact, reflecting the number of mesopores in the used material.